2016
DOI: 10.1039/c6sm01563h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the modulus of nanostructured ionomer films of core–shell nanoparticles based on poly(n-butyl acrylate)

Abstract: ABSTRACT:In this study we investigate the structure-mechanical property relationships for nanostructured ionomer films containing ionically crosslinked core-shell polymer nanoparticles based on poly(n-butyl acrylate) (PBA). Whilst nanostructured ionomer films of core-shell nanoparticles have been previously shown to have good ductility [Soft Matter, 10, 4725, 2014], the modulus values were modest. Here, we used BA as the primary monomer to construct core-shell nanoparticles that provided films containing nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Strategies to form mechanically strong films from waterborne polymer dispersions include the use of both chemical and physical crosslinking, but this complicates the chemistry of the system. Another possibility is to blend soft and hard polymer particles. However, this often leads to phase separation during film formation.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to form mechanically strong films from waterborne polymer dispersions include the use of both chemical and physical crosslinking, but this complicates the chemistry of the system. Another possibility is to blend soft and hard polymer particles. However, this often leads to phase separation during film formation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the formation of a percolating network between methacrylic acid containing latex (40% solid content, s.c.) and ZnO nanoparticles was reported, resulting in tunable mechanical properties [ 29 ]. Likewise, it was demonstrated that the addition of ZnO/KOH inorganic material into a latex containing methacrylic acid groups (45% s.c.) led to the formation of an ionic network that improved the elastic modulus of the material [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason is the so-called film formation dilemma of the waterborne coatings, that in order to form a good film, they need to have a low glass transition temperature ( T g ), but to achieve good mechanical properties, a high T g is needed. Out of the alternatives available to overcome this dilemma, the use of latexes comprising a soft core covered by patches of a hard polymer (this morphology is referred to as soft core–hard “shell”) is one of the more promising approaches. The advantage with respect to a well-defined soft core–hard shell morphology is that the particles with a discontinuous shell deform more easily during film formation and yield a film morphology consisting of a honeycomb structure of the hard polymer filled with the soft polymer. However, although this structure results in very good mechanical properties, , the presence of a hard polymer at the surface of the particles increases the stress generated during film formation that often results in cracking, , which is catastrophic for substrate protection. , It is worth mentioning that cracking occurs more easily in thick films, which are needed for demanding applications.…”
Section: Introductionmentioning
confidence: 99%